Understanding student variances in learning outcomes and task interpretations from multimedia presentations. (19th November 2018) - Dai, Yun; Liu, Ang
Abstract: This paper challenges a static view of the multimedia presentation as merely a final product for grading, and discusses how to elicit evidence‐based understandings about student learning from such a presentation. We present a micro‐ethnographic study investigating students' learning outcomes and task interpretations from multimedia presentations. The study was situated in a global technology‐enabled course, in which three groups of students delivered three different presentations, ie, a theatrical play, a short movie and a PowerPoint slideshow, for the same assignment. With video transcriptions and student interviews, we identified different degrees of learning outcomes achieved by the three groups at the collective level, and explained their variances in task interpretations behind the respective outcomes. Based on the findings, we further discussed the learning gap, task clarity, cultural difference and workload in relation to the presentations, along with implications for instructional practice and future research. Practitioner Notes What is already know about this topic The multimedia presentation has been widely used by students to report group work. The student presentation is often viewed as merely a final product for grading, while few studies have discussed how to elicit learning evidence from it. In examining student presentations, it is important to go beyond grading and understand the student interpretation regarding the task. What this paper adds The paper situated a multimedia presentation in an intertextual chain and proposed an empirical approach to examine the presentation. The study identified that the three groups of students achieved different degrees of learning outcomes at the collective level. The study found that the three groups' different learning outcomes were associated with their different interpretations of the task description. Implications for practice Instructors can adopt the micro‐ethnographic approach as an instructional tool to assess student learning in multiple dimensions from multimedia presentations. In designing a learning assignment, instructors should explicitly outline the rationale, expectation, and procedure in doing the assignment.